Evaluation of medicine prescription pattern using World Health Organization prescribing indicators in Iran: A cross-sectional study - Aliasghar Karimi; Malikeh Haerizadeh; Fatemeh Soleymani; Mahshid Haerizadeh; Forouzan Taheri (Wolters Kluwer Medknow Publications, 2014)
Objective: The objective was to quantify the specialists' prescription pattern in Iran and to point out the prescribing behavioral differences among several specialties. Methods: A retrospective cross-sectional study was carried out on the claim data. National prescription data were obtained on the basis of the claims that the pharmacies submitted to the insurers during 1 year period of the study. More than 85 million prescriptions were analyzed using "Rx-Analyst" software that is designed and applied by National Committee of Rational Use of Medicines in Iran. Specified medical specialties were considered and the World Health Organization prescription indicators were used to evaluate the physicians' prescribing behavior. Findings: Average items per prescription were ranged from 3.68 in cardiologists' to 2.06 in dermatologists' prescriptions. The highest and the lowest mean price were belonged to neurologists' and ophthalmologists' prescriptions, respectively. In addition, 45% of patients received antibiotics, 41% of patients received injectable form of drugs, and 23% received corticosteroids. A high tendency toward prescribing corticosteroids and antibiotics as well as an injectable form of medicines was observed among general physicians. Conclusion: There is an inevitable need to improve prescription habits among different specialties, especially among general practitioners. This causes the policymakers to put more emphasis on priorities such as continuous education.